Pengaurh Gaya Kepemimpinan, Disiplin Kerja, dan Motivasi Kerja Terhadap Produktivitas Guru pada SMKS PGRI Sampit Kabupaten Kotawaringin Timur - Wijayanti, Tatik; Sugianto, Sugianto (Mega Aktiva, 2024)
Productivity is the ability to produce products or results from organizational or company goals that have been designed and involve all aspects of management. The important factors that are concentrated in this research are Leadership Style, Work Discipline and Work Motivation in supporting the quality and quantity of work in each organizational unit. The research uses multiple linear regression analysis with the independent variables namely leadership style, work discipline and work motivation, while the dependent variable is work productivity. The results of this research are that leadership style has no effect on expected work productivity, work discipline variables do not affect work productivity while work motivation has a significant effect on work productivity. All research variables, namely leadership style, work discipline and work motivation simultaneously influence work productivity.